Household crowding during the COVID-19 lockdown fosters anti-democracy even after 17 months: A 5-wave latent growth curve study. (October 2022) - Russo, Silvia; Colloca, Pasquale; Cavazza, Nicoletta; Roccato, Michele
Abstract: In an earlier cross-sectional study, Roccato et al. (2021) showed that household crowding during the COVID-19 lockdown was positively related to support for anti-democratic political systems. However, little is known about the persistence of these effect over time. In this study, we examined its duration in a longitudinal study structured in five waves, the first in May–June 2019 (before the COVID-19 outbreak, N = 1504) and the others during the pandemic, in April 2020 (during the lockdown, N = 1199), October 2020 ( N = 1156), April 2021 ( N = 1148), and October 2021 ( N = 1151). The increase in support for anti-democratic systems associated with household overcrowding in the initial phase of the lockdown (Wave 2) did not change over the subsequent 17 months. Moreover, the effect was stronger among those who had high (compared with low) trust in democratic political institutions before the pandemic. Strengths, limitations, and potential developments of the study are discussed. Highlights: COVID-19 lockdown measures forced people to stay indoors 24/7. Household crowding during lockdown is associated with anti-democratic attitudes. This anti-democratic shift lasts at least 17 months. This anti-democratic shift is stronger among who was not anti-democratic before the pandemic. This study shows relevant socio-political consequences of household density.